2015
DOI: 10.3390/w7051769
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Water and Salt Exchanges in a Tidal Estuary

Abstract: A calibrated three-dimensional hydrodynamic model was applied to study subtidal water and salt exchanges at various cross sections of the Perdido Bay and Wolf Bay system using the Eulerian decomposition method from 6 September 2008 to 13 July 2009. Salinity, velocity, and water levels at each cross section were extracted from the model output to compute flow rates and salt fluxes. Eulerian analysis concluded that salt fluxes (exchanges) at the Perdido Pass and Dolphin Pass cross sections were dominated by tida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Subtidal salt transport using the Eulerian decomposition method has been studied in many estuaries to understand the mechanisms of material circulation [5][6][7][8][9][10]. These studies showed various mechanisms for estuarine circulation through salt transport analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Subtidal salt transport using the Eulerian decomposition method has been studied in many estuaries to understand the mechanisms of material circulation [5][6][7][8][9][10]. These studies showed various mechanisms for estuarine circulation through salt transport analysis.…”
Section: Introductionmentioning
confidence: 99%